Effect of nutrient management and row spacing on henna (Lawsonla inermis) leaf production and quality - Rao, S S; Regar, P L; Roy, P K; Singh, Y V (The Indian Journal of Agricultural Sciences, 2007)
A field experiment was conducted to find out the effect of conjunctive use of organics, ie farmyard manure and inorganic sources of nutrients and row spacing on henna (Lawsonia inermis L.) during 2003-04 to 2005-06 at Pali (Rajasthan). The application of farmyard manure of 5 tonnes/ha significantly increased dry leaf yield by 11.4% over no farmyard manure treatment. Fertilizer application at 80 kg N and 40 kg P2O5/ha recorded 19.3% higher dry leaf yield compared with the control. Significant improvement in dry leaf yield was also obtained with non-monetary input, ie increasing width of row spacing from 30 cm to 45 cm or 60 cm. Highest dry leaf yield of 1 302.6 kg/ha was obtained under 80 kg N and 40 kg P2O5/ha with 45 cm row spacing compared with the 945.2 kg/ha dry leaf yield obtained under 30 cm row spacing with no fertilizer. The results indicate that at higher levels of nutrient supply, more plants/unit area are required to exploit fully the higher fertility potentials. Leaf dye yield increased significantly due to application of farmyard manure, fertility levels and row spacing. Fertilizer at 80 kg N and 40 kg P2O5/ha gave Rs 14 749 net return compared to Rs 13 184 over no fertilizer application. The crop row spacing of 45 cm being at par with 60 cm gave net return as high as Rs 1 213/ha over 30 cm row spacing.